Find the value of x.
A.48
B.56
C.68
D.76
Find the value of x. A.48 B.56 C.68 D.76 - 1

Answers

Answer 1
Answer:

Answer:

A

Step-by-step explanation:

The secant- tangent angle 78° is half the difference of the intercepted arcs

(1)/(2) (204 - x) = 78 ( multiply both sides by 2 )

204 - x = 156 ( subtract 204 from both sides )

- x = - 48 ( multiply both sides by - 1 )

x = 48

Answer 2
Answer:

Answer:

A.) 48

Step-by-step explanation:

I got it correct on founders edtell


Related Questions

Write the expression (y 7)^2 -100 as the product of two linear binomials
Triangle ABC is similar to triangle QRS by the AA Similarity Postulate.Also, m∠A = 45° and m∠S = 75°.What is m∠B?_________ °
The function h(x) = –2x2 + 8x written in vertex form is h(x) = –2(x – 2)2 + 8. The function h(x) is shown on the graph along with the parent function, f(x) = x2.Which statement is true concerning the vertex and axis of symmetry of h(x)? The vertex is at (0, 0) and the axis of symmetry is x = 2. The vertex is at (0, 0) and the axis of symmetry is y= 2. The vertex is at (2, 8) and the axis of symmetry is x = 2. The vertex is at (2, 2) and the axis of symmetry is y = 2.
Please help with this Pythagoras' theorem Thank you
Is it true or false that any three points are contained in exactly one plane?

Help!The _______ is the key to deriving the equations for four conic sections.

Midpoint formula

Pythagorean theorem

Distance formula

Answers

Answer:

The correct answer is Distance Formula

Step-by-step explanation:

The shape of the conics in the conic section is characterized by a factor called eccentricity of the conic and further derivations are done using this factor.

And the eccentricity of the conics can be calculated by taking the center-to-focus distance and dividing it by the semi-major axis distance. So, to find the eccentricity of the conic, one must know how to apply the distance formula.

Hence, Distance Formula is the key to deriving the equations for conic sections

Answer:

answer is Distance Formula

Step-by-step explanation:

Determine the sum: 26.5 × 104 + 9.4 × 104. Write your answer in scientific notation.A. 17.1 × 104

B. 35.9 × 109

C. 3.59 × 105

D. 17.1 × 108

Answers

Answer:

\large\boxed{C.\ 3.59*10^5}

Step-by-step explanation:

\text{The scientific notation:}\n\na\cdot10^k,\ \text{where}\ 1\leq a<10\ \text{and}\ k\in\mathbb{Z}.\n--------------------\n\n\text{We have}\n\n26.5*10^4+9.4*10^4=(26.5+9.4)*10^4=35.9*10^4\n\n=3.59*10*10^4=3.59*10^5

A number x is no more than 9 units away from 8. Write and solve an absolute-value inequality to show the range of possible values of x.|x − 8| ≤ 9
−1 ≤ x ≤ 17

|x + 8| ≤ 9
−17 ≤ x ≤ 1

|x − 9| ≤ 8
1 ≤ x ≤ 17

|x + 9| ≤ 8
−17 ≤ x ≤ −1

Answers

Answer:

Option A is right

Step-by-step explanation:

Given that a number x is no more than 9 units away from 8

This implies that number can be either larger than 8 by less than 9 units or smaller than 8 by less than 9 units.

Difference between x and 8 is at most 9.

We represent in absolute value as

|x-8|\leq 9\n-9\leq x-8\leq 9\n-1\leq x\leq 17

Hence option A is right

The answer is a (|x - 8| ≤ 9 and -1 ≤ x ≤ 17) Because the difference between x and 8 can't be greater than 9, but it can be less than or equal to it, and because the range that x could be would be -1 to 17, since 8 + 9 = 17 and 8 - 9 = -1.

Simplify the expression (3/7)^2

Answers

The solution is 9/49

The value of the equation is A = 9/49

What is an Equation?

Equations are mathematical statements with two algebraic expressions flanking the equals (=) sign on either side.

It demonstrates the equality of the relationship between the expressions printed on the left and right sides.

Coefficients, variables, operators, constants, terms, expressions, and the equal to sign are some of the components of an equation. The "=" sign and terms on both sides must always be present when writing an equation.

Given data ,

Let the equation be represented as A

Now , the number be n = 3/7

The equation A = n²

Substituting the value for n in the equation , we get

A = ( 3/7 )²

On simplifying the equation , we get

A = ( 3 )² / ( 7 )²

The value of A = 9/49

Therefore , the value of A is 9/49

Hence , the equation is A = 9/49

To learn more about equations click :

brainly.com/question/19297665

#SPJ2

Answer:9/49


Step-by-step explanation: 3x3=9 7x7=49 so you get 9/49


An alloy weighing 40 lbs. is 10% tin. The alloy was made by mixing a 15% tin alloy and a 8% tin alloy. How many pounds of each alloy (to the nearest tenth) were used to make the 10% alloy?lbs. of the 15% alloy and lbs. of the 8% alloy.

Answers

Let the weight of 15% tin be  x.

So the weight of the 8% tin will be:  (40 - x), since the total weight is 40 lbs


Using the mixture formula:

w1*p1 + w2*p2 = w*p

Where w1 = weight of the first percentage, p1 = First Percentage

w2 = weight of the second percentage, p2 = Second Percentage

w = Final weight, p1 = Final Percentage

0.15*x + 0.08(40 - x) = 40*0.1

0.15x + 3.2 - 0.08x = 4

0.15x - 0.08x = 4 - 3.2

0.07x = 0.8

x = 0.8/0.07

x ≈ 11.429

Recall the 15% was made with x, which is ≈   11.429

Recall the 8% was made with (40-x) ≈  (40 - 11.429) ≈ 28.571

So the 10% tin of the 40 lbs was made with ≈11.4 lbs of the 15% tin and  ≈28.6 lbs of the 8% tin
x=15% alloy
y=8% alloy
x+y=40
y=40-x
0.15x+0.08y=40*0.10
0.15x+0.08(40-x)=40*0.1
times 100 both sides for easy
15x+8(40-x)=400
15x+320-8x=400
7x+320=400
minus 320 from both sides
7x=80
divide both sides by 7
x=80/7
x+y=40
80/7+y=280/7
y=200/7
aprox
x=11.4lb
y=28.6lb


11.4lb of 15%
28.6lb of the 8%
what????

What are the solutions to the equation x-7/x=6? a. x=-7 and x=1
b. x=-6 and x=-1
c. x=-1 and x=7
d. x=1 and x=6

Answers

x - (7)/(x) = 6
(x^(2))/(x) - (7)/(x) = 6
(x^(2) - 7)/(x) = 6
x^(2) - 7 = 6x
x^(2) - 6x - 7 = 0
x^(2) - 7x + x - 7 = 0
x(x) - x(7) + 1(x) - 1(7) = 0
x(x - 7) + 1(x - 7) = 0
(x + 1)(x - 7) = 0
x + 1 = 0    or    x - 7 = 0
x = -1    or    x = 7

Answer:

C


Step-by-step explanation:


The equation is x-(7)/(x)=6

LCM of the denominator on the left side gives us:

(x^(2)-7)/(x)=6

Cross multiplying and arranging gives us:

x^(2)-7=6x\nx^(2)-6x-7=0

This is a binomial, to factor this, we have to think of 2 numbers that multiplied gives us -7 [the constant term] and added gives us -6 [the coefficient of x].

The two numbers are: -7 and 1.

Now we can write:

x^(2)-6x-7=0\n(x-7)(x+1)=0

Hence, either (x-7)=0 OR (x+1)=0. This gives us two solutions, x=7 and x=-1. Answer choice C is correct.